Antara efikasi diri dan hasil belajar Pendidikan Agama Islam di Sekolah Menengah Atas - Aisyah, Siti Syifa; Amran (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2025)
Quality education requires an understanding of various factors that influence learning outcomes, including internal psychological aspects such as self-efficacy. This study aims to determine the level of self-efficacy, the learning outcomes in Islamic Religious Education (PAI), and the relationship between the two among 11th-grade science students at SMAN 1 Tamansari, Bogor Regency. This research employed a descriptive quantitative approach with a population of 36 students. Self-efficacy data were collected using a Likert-scale questionnaire consisting of 40 statements, while learning outcomes were measured through students' report card grades. The results showed that students' self-efficacy was categorized as very high, with an average score of 120.13 and 94% of students demonstrating high self-efficacy levels. Meanwhile, the average learning score for PAI was 88.86, with 97% of students achieving scores above the Minimum Competency Criteria (KKM). However, the Pearson correlation test indicated no significant relationship between self-efficacy and PAI learning outcomes (r = -0.230; sig. = 0.176). Although the relationship is linear, the correlation is weak and statistically insignificant. These findings suggest that self-efficacy does not directly affect learning outcomes, and other factors may significantly contribute to students’ academic achievement. Abstrak Pendidikan yang bermutu memerlukan pemahaman terhadap berbagai faktor yang mempengaruhi hasil belajar, termasuk faktor psikologis internal seperti efikasi diri. Penelitian ini bertujuan untuk mengetahui tingkat efikasi diri, hasil belajar Pendidikan Agama Islam (PAI), serta hubungan antara keduanya pada siswa kelas XI MIPA di SMAN 1 Tamansari, Kabupaten Bogor. Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan populasi sebanyak 36 siswa. Data efikasi diri diperoleh melalui angket skala likert sebanyak 40 butir pernyataan, sedangkan hasil belajar diukur menggunakan nilai rapor. Hasil penelitian menunjukkan bahwa efikasi diri siswa berada pada kategori sangat baik dengan rata-rata skor 120,13, dan sebanyak 94% siswa menunjukkan tingkat efikasi diri tinggi. Sementara itu, hasil belajar PAI menunjukkan rata-rata nilai sebesar 88,86, dengan 97% siswa mencapai nilai di atas KKM. Namun, hasil uji korelasi Pearson menunjukkan tidak terdapat hubungan yang signifikan antara efikasi diri dan hasil belajar PAI (r = -0,230; sig. = 0,176). Meskipun hubungan bersifat linier, korelasinya lemah dan tidak signifikan. Temuan ini menunjukkan bahwa efikasi diri tidak secara langsung memengaruhi hasil belajar, dan faktor lain kemungkinan turut berperan dalam pencapaian akademik siswa.